1968
DOI: 10.1107/s0567740868003511
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of pyroaurite

Abstract: Rhombohedral pyroaurite (Rgm, a=3.1094+2, c=23.4117+9 A, at 21°) consists, like hexagonal sj6grenite (P6/mmc, a=3.113+3, c=15"61+1/~), of positively charged brucite-like layers [Mg6Fe~(OH)16] z+ alternating with disordered negatively charged interlayers [CO3.4H20]E-(Z= ~t for pyroaurite). Mg and Fe are randomly distributed among the octahedral positions. The OH layer sequence in pyroaurite is -BC-CA-AB-BC-. The water molecules of the (liquid-like) interlayer prefer positions about 0.56 A off the threefold axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
241
0
23

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(278 citation statements)
references
References 2 publications
(3 reference statements)
8
241
0
23
Order By: Relevance
“…The lines are explained in the text. The data are from the following references: (1) For single crystals: Allmann (1968Allmann ( , 1969) (pyroaurite and 'sjö grenite'); Arakcheeva et al calculated lines are strikingly similar to those from the regression analysis of the experimental data, which supports strongly the geometrical approach developed in this paper, together with the values determined for r(OH À (IV)) and the bond angle . The same value of is again appropriate with either trivalent ion, in agreement with the observation for the Ni-based systems; i.e.…”
Section: Layered Double Hydroxidessupporting
confidence: 71%
See 1 more Smart Citation
“…The lines are explained in the text. The data are from the following references: (1) For single crystals: Allmann (1968Allmann ( , 1969) (pyroaurite and 'sjö grenite'); Arakcheeva et al calculated lines are strikingly similar to those from the regression analysis of the experimental data, which supports strongly the geometrical approach developed in this paper, together with the values determined for r(OH À (IV)) and the bond angle . The same value of is again appropriate with either trivalent ion, in agreement with the observation for the Ni-based systems; i.e.…”
Section: Layered Double Hydroxidessupporting
confidence: 71%
“…6(d) suggests that there is a problem with the chemical composition assumed by Allmann (1968) for pyroaurite, i.e. x = 0.25.…”
Section: Substitution By Two Different Types Of Trivalent Cationsmentioning
confidence: 99%
“…Os valores dos parâmetros a e c foram obtidos segundo as Equações propostas por Debye-Scherrer. [22][23][24][25][26] O parâmetro c foi calculado através da multiplicação de d(003) em Å pelo índice 3, ou seja, c = 3d 003 . O parâmetro a foi calculado por meio da multiplicação de d(110) em Å por 2, isto é, a = 2d 110 .…”
Section: Espectroscopia Vibracional Na Região Do Infravermelho (Eiv)unclassified
“…Low-cost materials, in their natural and modified forms, have been also extensively studied as alternative adsorbents for dyes (Ahmad et al 2007;Gurses et al 2006). Among the different adsorbents, layered double hydroxides (LDHs), also known as hydrotalcite-like compounds or anionic clays, are promising waste scavengers, particularly for dye molecules (Allmann 1968). Recent studies showed that the use of LDHs for the retention of organic anions has given very good results (De Roy et al 1992;Lakraimi et al 2000).…”
Section: Introductionmentioning
confidence: 99%